Analisis Wacana Stereotip Perempuan dalam Berita Kriminal di Viva.co.id - Rizky Abiyyah; Farida Hariyati; Sri Mustika (STIKes Ibnu Sina Ajibarang, 2024)
Mass media plays a significant role in shaping public perceptions of issues such as sexual and domestic violence. This study focuses on how text structure, word choice, and gender representation in news articles influence public understanding of violence. The aim of this research is to analyze how news about sexual violence and domestic violence constructs narratives and social responses through language use and text structure, and how gender representation affects public perception. The study employs critical discourse analysis based on Norman Fairclough's theory. Two news articles were selected for analysis: one about sexual violence in front of a young girl and one about domestic violence. The articles were examined for text structure, word choice, and gender representation to understand how they construct narratives. The analysis reveals that the news about sexual violence emphasizes the perpetrator's actions and the authorities' responses, using sensational language to create a negative image of the perpetrator. In contrast, the news about domestic violence focuses more on the victim's suffering and power dynamics, with detailed descriptions of physical and emotional abuse. Media shapes public perceptions of violence and gender through word choice and text structure.